Preparation of polyaniline polymer and using it as a Vapor sensor of acids - Jabor, Ashwaq A. (Iraqi Journal of Physics, 2019)
Polyaniline organic Semiconductor polymer was prepared by oxidation polymerization by adding hydrochloric acid concentration of 0.1M and potassium per sulfate concentration of 0.2M to 0.1M of aniline at room temperature, the polymer was deposited at glass substrate, the structural and optical properties were studies through UV-VIS, IR, XRD measurements, films have been operated as a sensor of vapor H2SO4 and HCl acids.